Agile Code Board: An Integrated Task, Planning, and Brainstorming Tool for Agile Teams - T. Vignesh; J.V. Johnsonselva (International Journal Software Engineering and Computer Science (IJSECS), 2025)
Agile methodologies are widely adopted in software development for their effectiveness in team coordination, iterative progress, and comprehensive project oversight. This study analyzes the Agile Code Board, a real-time project management platform designed to assist Agile teams in organizing and executing tasks throughout each sprint. The platform offers multiple workspaces with role-based access, enabling task tracking, immediate team collaboration, and sprint-level planning. Key features include a drag-and-drop Kanban board, a collaborative whiteboard, calendar integration for deadlines and milestones, a filterable task table, and a cross-team program board inspired by SAFe. Agile Code Board is built using Next.js and Hono, with Appwrite for authentication and Liveblocks for real-time collaboration. The system introduces mechanisms that facilitate efficient teamwork and project coordination. This research outlines the system architecture, development practices, and the ways in which the platform enhances Agile workflow management in collaborative environments.